Falco rusticolus (Falconidae) - Aufzucht der Jungen - Lammers, Rudolf; Lammers, Friedhelm (IWF (Göttingen), 1980)
In drei verschiedenen Biotopen werden adulte Gerfalken und ihre Jungen in drei Altersstufen beobachtet (Hudern, Beutebringen, Füttern, Fliegen der Adulten, Flugübungen der Jungen). Die biotopabhängigen Beutevögel (Schneehühner, Wassergeflügel) werden vorgestellt. : The raising of young is documented showing three eyries of the Falco rusticolus in the north-west of Iceland. Two breeding places inland are compared with an eyrie on the coast. Simultaneous shots give a comparison of the difference in ages of the young birds. Special attention is paid to the development of prey, in particular that of the snow grouse (ptarmigan) and the significance for the inland population.